Status Sosial Wanita di Era Georgian dalam Novel EMMA Karya Jane Austen - Khalfia Dwi Hardiyanti; Saprudin (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2021)
This research is entitled "Social Status of Women in the Georgian Era in Jane Austen's EMMA Novel". This study aims to describe women’s life and the social status of women in the Georgian Era of England in the 18th century. This research uses the theory of social background according to Warren and Wellek (2013) and the theory of social status according to Teeuw (2010). This study uses descriptive qualitative research methods and uses a literary approach to describe the women’s life and the social status of women in England in Georgian Era. This study also uses data collection, reading, listening, and taking notes. The results of this study are a description of women’s life and the social status of women in England in Georgian Era through the main character Emma Woodhouse and other female characters based on their social background.Based on the analysis that the author conducted on the description of women's lives in the Georgian Era in Jane Austen's novel EMMA, namely the female characters in this Era enjoy visiting, they also like to play music and attend a party or dinner invitation which aims to attract men's attention. They love to show off their skills. Women in this era if other skills such as painting or painting are good at playing music, it means they get from the upper class because they get a good education.